The Pandemic Fall of the Sky: contagions between the Palace and the Forest - Pitta, Maurício Fernando (2024)
What it means to say, as did the group Indigenous Action among the covid-19 pandemics, that “capitalism is pandemic” and that “we [indigenous peoples] are the antibodies”? What are the ties between pandemic crisis, the capitalism in its global phase and the climate emergency known as “the Anthropocene”? How is this nexus seen by those, such as indigenous peoples, that, albeit at the peripheries of this process, are the most affected by its harmful effects? With this provocation and the many articulations between merchandise, epidemics (xawara) and the end of the world (“the falling sky”) made by Davi Kopenawa in his dialogue with Bruce Albert, we aim to think in this essay on the relationship between capitalism and catastrophe with the key notion of “contagion”. We suspect that, in its intentional repetition of the word “xawara” all over The Falling Sky, Kopenawa is not just utilizing a technical word to epidemical diseases in general, but conceptually marking the kind of “immunological” relation white people (napë pë), also known as “people of merchandise” among the Yanomami, forge with otherness in general.